STN1 facilitates metastasis by promoting transcription of EMT-activator ZEB1 in pancreatic cancer - Dong, Di; Zhou, Zhe; Zhu, Minglu; Hou, Zhiyuan; Chen, Mo; Gong, Jingjing; Zhao, Xuyang; Yan, Aohui; Liang, Hui; Yin, Yuxin (Nature communications, 2025)
Pancreatic ductal adenocarcinoma (PDAC) poses a serious clinical challenge, demanding further exploration of its pathogenesis and therapeutic targets for metastasis, the main cause of mortality. Here, we identify STN1, a CST complex member crucial for maintaining telomere lengths and genome stability, as a key factor in promoting PDAC metastasis. Elevated STN1 levels correlate with poor patient survival, with oncogenic protein HOXB7 as an upstream transcription factor regulating STN1 . Utilizing multiple PDAC experimental models, we discover STN1’s role in promoting metastasis by functioning as an upstream factor in epithelial-mesenchymal transition (EMT). Our mechanistic evidence suggests that during transcription, STN1 binds to structurally displaced single-stranded DNA flanking the R-loop, recruiting STAT3 to activate ZEB1 transcription independent of its known telomere maintenance function. Notably, STAT3 inhibitors show enhanced efficiency in restraining metastatic potential in STN1-overexpressed PDAC cells, offering a potential therapeutic avenue for targeting metastasis in STN1-overexpressed PDAC patients facing an unfavorable prognosis. Metastasis of pancreatic cancer has been associated with epithelial-mesenchymal transition (EMT). Here, the authors identify STN1 as a regulator of pancreatic cancer metastasis by promoting transcription of EMT-activator ZEB1, which is independent of its known role in telomere maintenance.